Steam pasteurization of commercially slaughtered beef carcasses: Evaluation of bacterial populations at five anatomical locations - Nutsch, Abbey L.; Phebus, Randall K.; Riemann, M. James; Kotrola, John S.; Wilson, R. Craig; Boyer, John E.; Brown, Ted L. (My University, 2008)
A steam pasteurization process (patent pending) has been shown to effectively reduce pathogenic bacterial populations on beef tissue and to significantly reduce naturally occurring bacterial populations on commercially slaughtered beef carcasses. The objective of this study was to determine the effectiveness of the steam pasteurization treatment for reducing bacterial populations at several anatomical locations on commercially slaughtered carcasses. Before and after pasteurization treatment (82.2°C, 6.5-s exposure time), a sterile sponge was used to sample 300 cm2 at one of five locations (inside round, loin, midline, brisket, or neck). Eighty carcasses (40 before treatment and 40 after treatment) were sampled per anatomical location over 2 processing days. Before treatment, aerobic plate counts (APCs) were found to be highest (P ≤ 0.01) at the midline (4.5 log10 CFU/100 cm2), intermediate at the inside round, brisket, and neck (ca. 3.8 log10 CFU/100 cm2), and lowest at the loin (3.4 log10 CFU/100 cm2). After treatment, APCs at all locations were reduced significantly (P ≤ 0.01). The inside round, loin, and brisket had the lowest (P ≤ 0.01) APCs (ca. 2.6 log10 CFU/100 cm2), whereas the midline and neck had APCs of 3.1 and 3.3 log10 CFU/100 cm2, respectively. The lower reduction in APCs at the neck area indicated that the treatment may not be as effective there, possibly because of the design of the pasteurization equipment. Generic Escherichia coli populations were low at all locations before treatment, with populations on 32% of all carcasses sampled being less than the detection limit of the study (5.0 CFU/100 cm2). After treatment, E. coli populations were significantly lower (P ≤ 0.01) than populations before treatment and 85% of all carcasses sampled had E. coli populations below the detection limit. The maximum E. coli population detected after treatment was 25 CFU/100 cm2. For enteric bacterial populations, no differences were observed in the effectiveness of the treatment among the five carcass locations.
Keywords: Beef; Steam; Pasteurization; Decontamination; E. coli; Pathogens